2011
DOI: 10.1111/j.1553-2712.2011.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Computer Kiosk–expedited Management of Cystitis in the Emergency Department

Abstract: Objectives: The objective was to assess the efficiency and safety of an interactive computer kiosk module for the management of uncomplicated urinary tract infections (UTI) in emergency departments (EDs).Methods: This was a prospective unblinded randomized trial. Women age 18 to 64 years seeking care for suspected UTI in three urban EDs were referred to a computer kiosk after triage. The kiosk evaluated women for uncomplicated UTI (based on patient report of at least one irritable voiding symptom within 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Huppert et al (5) found that only 26% of adolescent women presenting to the ED with urinary symptoms had a positive urine culture. Even in a selected group of women presenting to several EDs with a history of UTI, irritable-voiding symptoms, and absence of vaginitis and complicating factors, a group comprising only 17% of the women presenting with suspected UTIs, Stein et al (20) found that only 69% had a positive urine culture. Other etiologies of traditional UTI symptoms without vaginal symptoms would include infection with herpes simplex virus, other viruses, Mycoplasma genitalium, and Ureaplasma urealyticum, as well as noninfectious causes such as vaginal atrophy, urethral trauma during sexual intercourse or other physical activity, sensitivity to topical perianal products, nephrolithiasis, and psychogenic conditions (21).…”
Section: Discussionmentioning
confidence: 99%
“…Huppert et al (5) found that only 26% of adolescent women presenting to the ED with urinary symptoms had a positive urine culture. Even in a selected group of women presenting to several EDs with a history of UTI, irritable-voiding symptoms, and absence of vaginitis and complicating factors, a group comprising only 17% of the women presenting with suspected UTIs, Stein et al (20) found that only 69% had a positive urine culture. Other etiologies of traditional UTI symptoms without vaginal symptoms would include infection with herpes simplex virus, other viruses, Mycoplasma genitalium, and Ureaplasma urealyticum, as well as noninfectious causes such as vaginal atrophy, urethral trauma during sexual intercourse or other physical activity, sensitivity to topical perianal products, nephrolithiasis, and psychogenic conditions (21).…”
Section: Discussionmentioning
confidence: 99%
“…This includes an acknowledgment that success and failure are socially negotiated e and often contested e categories (Berg, 2001). In the case of the kiosk, the researchers considered the study a success, and they published a report suggesting that the kiosk "accurately, efficiently, and safely expedited the management of women with uncomplicated UTI in a busy, urban ED" (Stein et al, 2011). ED staff, on the other hand, generally considered the kiosk to be a failure, and their "triage" of the kiosk resulted in the device's being "unplugged" at all but the home site by the end of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Results of a randomized trial at three of the four EDs confirmed the accuracy of the kiosk algorithm's diagnosis and treatment recommendations, and demonstrated that it reduced wait time among women who received kiosk-assisted services (Stein et al, 2011). However, attempts to integrate the kiosks into routine practice encountered unexpected difficulties at all sites, including uneven recruitment patterns, staff resistance, and lower than anticipated patient eligibility for kiosk-assisted services.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations